Tracing the Evolution of Digital Storytelling in Cultural Studies: A 19-Year Bibliometric Analysis - Rina Latifah, Siti; Damayani, Ninis Agustini; Winoto, Yunus (Program Studi Ilmu Perpustakaan UIN Alauddin, 2025)
This study aims to analyze the production and scholarly trends of Scopus-indexed scientific research on digital storytelling in the context of cultural studies using a bibliometric approach. Data were analyzed using Bibliometrix-R through the Biblioshiny interface and visualized with VOSviewer (version 1.6.20). The findings indicate that scholarly attention to digital storytelling peaked in 2019, with the highest average citations per article at 3.83. However, average citation rates declined in subsequent years, reaching 1.92 in 2023 and 0.79 in 2024. Among contributing scholars, Benmayor received the highest citation count for the article titled “Digital storytelling as a signature pedagogy for the new humanities” published in Arts and Humanities in Higher Education in 2008. Keyword analysis reveals that “digital storytelling,” “storytelling,” and “human” are the most frequently occurring terms, reflecting core thematic concerns in this field. These results suggest a sustained yet evolving interest in digital storytelling within cultural studies, and they underscore the need for further research on its pedagogical and cultural implications in contemporary discourse.